Strategi Pengembangan Usaha Produk UD. Amelia Bakery Tabanan - Sukarmini, Ni Luh Wayan Ari; Wrasiati, Luh Putu; Yoga, I Wayan Gede Sedana (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 9 No 2 (2021): JuniDO - 10.24843/JRMA.2021.v09.i02.p07, 2021)
Amelia Bakery is a business that is engaged in food, especially bread and cakes. Amelia Bakery located Jl.Tukad Sang-sang, Banjar Dinas Sanggulan 2 No.1 Jadi Anyar, Kediri District, Tabanan Regency. Amelia Bakery produce brownies and muffins. The high competition is one of the factors to carry out product development strategies. The purpose of thisstudy are: 1) To determine theinternal (strengths and weakness) and external (opportunities and threats) factorsfaced in marketing at UD. Amelia Bakery, 2) Determining alternative strategies that can be used for product business development at UD. Amelia Bakery, 3) Determine the priority of product business development strategies at UD. Amelia Bakery. This study uses the SWOT method to determine the alternative strategies used, and TOPSIS to rank these alternatives. The strategies that can be applied in UD. Amelia Bakery Tabanan is a strategy to hold and maintain, where the alternative strategies are as follows: a) Improve product quality, b) Increase the variety or type of product being promoted, c) Maintain consistency of product quality, d) Training for employees, e) Making packaging that is more attractivet. Keywords : UD. Amelia Bakery, brownies and muffins, SWOT analysis, TOPSIS Method